Hearing rehabilitation outcomes in cochlear implant recipients with vestibular schwannoma in observation or radiotherapy groups: A systematic review. (2nd January 2020) - Borsetto, Daniele; Hammond-Kenny, Amy; Tysome, James R.; Axon, Patrick R.; Donnelly, Neil P.; Vijendren, Ananth; Phillips, Veronica; Bance, Manohar L.
Abstract : Objectives: Vestibular schwannomas (VS) are rare benign tumours of the vestibular nerve that cause hearing loss. Management strategies include watchful waiting, radiotherapy or surgical resection. Historically, the presence of retrocochlear disease has been considered to be a contra-indication to cochlear implantation (CI). The aim of this systematic review is to assess hearing rehabilitation outcomes for CI recipients with VS, either sporadic or associated with neurofibromatosis type 2, whose tumours have been managed with either observation or radiotherapy. Methods: PubMed, Embase, and Cochrane Library databases were searched from inception through to November 2018. 50 cases from 12 studies met the inclusion criteria. Patient demographics, VS characteristics, management strategy, pre-CI hearing status, electrical promontory stimulation testing, post-CI hearing status and speech perception scores, functional benefits and follow-up length are reported. Results: Radiotherapy and observation groups had similar patient demographics in terms of age at CI, tumour size and duration of deafness. Following CI, 64% and 60% of patients in the radiotherapy and observation groups achieved open-set speech perception, respectively. Pure tone average thresholds (33 vs. 39 dB) and speech scores were also comparable between both groups. Conclusion: Ipsilateral CI in patients with VS that have not been surgically resected can provide beneficial hearing rehabilitation outcomes.